Viability of different feed rates for Astyanax bimaculatus culture - Jatobá, Adolfo (2018)
The objective of this study was to evaluate the growth performance and cost of Astyanax bimaculatus (yellow tail lambari) fed with different feeding rates. For such, 720 (4.06 ± 0.33 g) juvenile fish were fed with four different feeding rates (2.5, 4.0, 5.5, and 7.0% of biomass). After six weeks, growth performance and cost of the fish produced (in kg) were evaluated. Fish fed with 4.0 and 5.5% of the biomass showed the best growth performance and financial results; thus, these feed rates are the most attractive for Astyanax bimaculatus culture.